Conformational diversity in class C GPCR positive allosteric modulation - Giuseppe Cannone; Ludovic Berto; Fanny Malhaire; Gavin Ferguson; Aurelien Fouillen; Stéphanie Balor; Joan Font-Ingles; Amadeu Llebaria; Cyril Goudet; Abhay Kotecha; Vinothkumar K.R.; Guillaume Lebon (Nature Communications)
Abstract The metabotropic glutamate receptors (mGlus) are class C G protein-coupled receptors (GPCR) that form obligate dimers activated by the major excitatory neurotransmitter L-glutamate. The architecture of mGlu receptor comprises an extracellular Venus-Fly Trap domain (VFT) connected to the transmembrane domain (7TM) through a Cysteine-Rich Domain (CRD). The binding of L-glutamate in the VFTs and subsequent conformational change results in the signal being transmitted to the 7TM inducing G protein binding and activation. The mGlu receptors signal transduction can be allosterically potentiated by positive allosteric modulators (PAMs) binding to the 7TMs, which are of therapeutic interest in various neurological disorders. Here, we report the cryoEM structures of metabotropic glutamate receptor 5 (mGlu5) purified with three chemically and pharmacologically distinct PAMs. We find that the PAMs modulate the receptor equilibrium through their different binding modes, revealing how their interactions in the 7TMs impact the mGlu5 receptor conformational landscape and function. In addition, we identified a PAM-free but agonist-bound intermediate state that also reveals interactions mediated by intracellular loop 2. The activation of mGlu5 receptor is a multi-step process in which the binding of the PAMs in the 7TM modulates the equilibrium towards the active state.